The Social Amplification of Risk: Perceived Threats to Medical Workers in War Zones - Shahin Farzaneh; Nasrin Abdul Golshani (Inovasi Analisis Data, 2025)
Objective: The objective of this study is to examine the determinants of public perception regarding the safety of medical workers in conflict zones.Methods: We employed a quantitative cross-sectional design, using a structured questionnaire that we distributed to a diverse sample. Regression and moderation analyses were performed on the data to test the hypothesised relationships.Findings: The results demonstrate that the perceived threat to medical workers' safety is significantly influenced by media exposure intensity, belief in international humanitarian law, and public trust in healthcare institutions. Furthermore, political affiliation moderates these relationships. It does so by strengthening the effect of media exposure. At the same time, it weakens the influence of humanitarian law beliefs. The filter used to select media sources also moderates the relationship between public trust and perceived threat. The integrated model sheds light on significant differences in public opinion, highlighting the intricate relationship between information exposure, societal standards, institutional trust, and personal filters.Novelty: This research proffers a pioneering integrated framework that concurrently evaluates the immediate consequences of pivotal determinants and the incidental functions of political affiliation and media source filter. It provides new information about how ideas and thinking affect how people see humanitarian rules in places where there is conflict, and it does this in a new way that is different from the usual ways of thinking.Research Implications: The findings offer crucial theoretical contributions by validating an integrated model of perception formation. In practice, they help humanitarian organisations develop communication strategies that are nuanced and take into account political affiliations and media consumption patterns. The aim is to effectively advocate for the protection of medical workers.